TRANSFORMATION IN BRUCE ALMIGHTY AND GOD TUSSI GREAT HO: AN INTERTEXTUALITY STUDY - Ayu Istiqomah (English Teaching Journal : A Journal of English Literature, Language and Education, 2015)
The purpose of this research is to describe the intertextuality in transforming the portrayal of God in two movies entitled Bruce Almighty and God Tussi Great Ho. The transformation is seen in portraying God in Bruce Almighty which uses Zeus God and in God Tussi Great Ho which uses Siva God. It is influenced by believes which occurs the culture of those movies. This research uses qualitative method. The researcher collects the primary data is from movies and secondary data is from Kristeva’s intertextuality. The analysis of this study takes some phenomena in both of two films which are going to same identify supporting by other references about American and Indian culture. Then, analyzes all of them, interprets them in description. The conclusion is the portraying of imitation God in both of two movies use some names, color symbolism, and God’s character in same way.